Comparison of Two Citizen Scientist Methods for Collecting Pond Water Samples for Environmental DNA Studies. (21st August 2018) - Buxton, Andrew; Groombridge, Jim; Griffiths, Richard
The use of environmental DNA (eDNA) for the survey of aquatic species offers a wide range of benefits over conventional surveys and has begun to be used by citizen scientists. One advantage of eDNA over conventional survey protocols is the comparative ease with which samples can be collected over a wide geographic area. However, eDNA collection protocols vary widely between different studies, promoting a need to identify an optimum method. Collection protocols include ethanol precipitation and various filtration methods including those that use electronic vacuum or peristaltic pumps, hand pumps, or syringes to capture eDNA on a membrane. We compare the effectiveness of two eDNA collection methods suitable for use by citizen scientists: Glass-microfiber syringe filtration and ethanol precipitation. Paired samples of water were analysed for Great Crested Newt ( Triturus cristatus ) DNA using (1) a laboratory tank experiment using different dilutions of water inoculated with newt DNA; and (2) by sampling naturally colonised ponds. Although syringe filters consistently yielded greater DNA extract concentrations in the tank experiments, this was not the case in samples collected from the field where no difference between the two methods was identified. Clearly, properties within the water—such as algae and particulate matter—can influence the amount of DNA captured by the two methods, so the sampling protocol of choice will depend on the design and goals of the study.